Influence of Public Revenues on Economic Growth The Case of the Republic of North Macedonia - Aleksandar Nikoloski (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2020)
The economy in each country performs different functions of a political, social and economic nature, in order to improve social and economic well-being. Public revenues affect economic growth by meeting various government needs. Taxes fully create discouraging effects on economic growth, especially those that reduce the incentive to invest in physical and human capital and innovation. The purpose of this research is to see the connection between public revenues and economic growth in the Republic of Macedonia and to determine the impact of tax and non-tax revenues on the growth of the country. With the help of econometric modeling, it was found that the observed public revenues as a whole affected the economic growth with 90, 2%, which is a high percentage. Individually, customs duties, VAT and direct taxes have a positive impact, and non-tax revenues and contributions negatively affect the economic growth of the republic.